Removal Water Turbidity by Crumb Rubber Media - Sulaymon, Abbas H.; Abdul-Ahad, Muna Yousif; Alwared, Abeer I. (Al-Khwarizmi Engineering Journal, 2017)
Abstract The removal of water turbidity by using crumb rubber filter was investigated .The present study was conducted to evaluate the effect of variation of influent water turbidity (10, 25 and 50 NTU), media size (0.6and 1.14mm), filtration rate (25, 45 and 65 l/hr) and bed depth (30 and 60 cm) on the performance of mono crumb rubber filter in response to the effluent filtered water turbidity and head loss development, and compare it with that of conventional sand filter.Results revealed that 25 l/hr flow rate and 25 NTU influent turbidity were the best operating conditions. smaller media size and higher bed depth gave the best removal efficiency while higher media size and small bed depth gave lower head loss. The optimum results show that 92.7% removal efficiency and 8.3 mm head loss. The comparison results show that at constant operating conditions, pressure drop for crumb rubber filter is lower than conventional sand filter; about 42% reduction in pressure drop than sand filter and the conventional sand filter has a little enhancement in removal efficiency than crumb rubber filter, 96.8% for sand while for crumb rubber 92.7%. Keywords: Turbidity; filtration; crumb rubber media; head loss.